Fabrication and characterization of novel glass-ionomer cement prepared from oyster shells - Kifayah K. Thbayh; Rafid M. AlBadr; Kareema M. Ziadan; Dalal K.Thbayh; Shaimma M. Mohi; Bela Fiser; Фішер Бейло; Fiser Béla (Springer Nature, 2024)
Abstract. Glass ionomer cement (GIC) is one of the most widely used restorative materials for temporary fillings and reconstructions in dentistry, but it has relatively poor mechanical properties that make its use limited, especially in places subject to high pressure. Thus, to extend the applicability of GIC, samples based on SiO2, P2O5, Al2O3, CaF2, and NaF were prepared with the addition of calcium oxide CaO extracted from natural sources (oyster shells) in different ratios of 0, 5, 10, 15, 20, and 25% wt. The suggested glass samples were evaluated, and their physical and mechanical properties were compared. XRD, SEM, and FTIR were performed on the samples. 24 specimens were prepared for each test in order to assess the mechanical properties as per the specific requirements. The tests included measuring bending strength, elastic modulus, adjusted direct tensile strength, absorption, water solubility, and diffusion coefficients after the specimens were stored in distilled water for 60 days. All calculations were carried out in accordance with standard procedures. The findings indicated a slight improvement in the bending resistance of the recommended GIC. Glass modified with 20% by weight of calcium oxide was the best among the ratios in terms of the results obtained and compared to the traditional commercial type. The malleable strength of the sample was 54.121 MPa, while the flexural modulus increased, the tensile strength reached 10.154 MPa, and the solubility was 25.87 µg/mm3 after storage for 60 days. These indicate that the developed material is suitable for use as a dental restoration material when compared to international commercial cement specifications.
Editors: https://www.nature.com/srep/about/editors
Contents: https://www.nature.com/srep/research-articles?year=2024
Keywords: GIC; Dental fillings; Oyster shells; Physical properties; Dental restoration; CaO